2015
DOI: 10.1007/978-1-4939-2453-0_18
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Induced Gene Silencing as a Scalable Tool to Study Drought Tolerance in Plants

Abstract: Here we describe the methodology of using virus-induced gene silencing (VIGS) as a powerful and scalable tool to screen the function of genes that participate in adaptation to drought. Silencing of endogenous gene expression in Nicotiana benthamiana is achieved by systemic infection of the aerial parts of the plant with a virus engineered to contain homologous fragments of the target gene(s) of interest. Silenced plant material can be consistently produced with little optimization in less than 1 month without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Vacuum agroinfiltration has been used in VIGS systems in various previous studies (Tague and Mantis, 2006; George et al, 2010, 2012, 2015; Kirigia et al, 2014; Tian et al, 2014). In the experiments reported here it was applied using 20 mL syringes and 10 mL medical glass bottles ( Figures 1B , 2B and Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vacuum agroinfiltration has been used in VIGS systems in various previous studies (Tague and Mantis, 2006; George et al, 2010, 2012, 2015; Kirigia et al, 2014; Tian et al, 2014). In the experiments reported here it was applied using 20 mL syringes and 10 mL medical glass bottles ( Figures 1B , 2B and Supplementary Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum-aided agroinfiltration has proven ability to increase infection efficiency in genetic transformation and VIGS procedures, especially for plants that have high resistance to infiltration (Tague and Mantis, 2006; George et al, 2010, 2012, 2015; King et al, 2014; Tian et al, 2014). Thus, we employed vacuum-aided agroinfiltration and found that applying it for 30 and 60 s resulted in the highest silencing efficiencies for wheat and maize, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virus-induced gene silencing is a valuable tool that can effectively silence individual genes or families of genes critical for plant development or resistance to biotic and abiotic stresses ( George et al, 2015 ). This tool is a simple and rapid method for assessing gene function ( Burch-Smith et al, 2004 ; Robertson, 2004 ; Becker and Lange, 2010 ; Cakir et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%